Crying Wolf: A Qualitative Review of Misinformation and Conspiracy Theories in Lupus Erythematosus. (June 2023) - Porter, Emma; Murphy, Michelle; O'Connor, Cathal
Background: Lupus comprises a complex group of inflammatory disorders including cutaneous lupus erythematosus (CLE) and systemic lupus erythematosus (SLE). The issue of health misinformation is increasingly problematic, although the content of misinformation related to lupus available online has not been deeply explored. This study aimed to qualitatively assess the type of misinformation related to lupus available online. Methods: A literature search on PubMed was conducted, using search terms "cutaneous lupus" OR "discoid lupus" OR "lupus" AND "misinformation" OR "conspiracy" OR "disinformation." Further searches were also performed on Google, YouTube, Twitter, Facebook, Instagram, and TikTok. Results: Published literature describing lupus-related misinformation was minimal, with only three manuscripts identified. Conversely, a variety of points of misinformation were identified online and on social media. Key themes identified in online content included suggestion of incorrect causes such as infection or aspartame consumption, false risk assessments such as lupus never developing in males, false claims about conventional treatments, and promotion of alternative treatments or "cures" without evidence. Conclusion: Dermatologists, rheumatologists, and all clinicians treating patients with lupus play an essential role in dispelling the pervasive misinformation surrounding the disease and its treatments, encouraging patients to seek reliable sources of information, and advocating for evidence-based guidance.